Bridging theory and practice: Mixed methods approach to instruction of law and ethics within the pharmaceutical sciences - Wilby, Kyle John (2016)
Background: Professional responsibilities are guided by laws and ethics that must be introduced and mastered within pharmaceutical sciences training. Instructional design to teaching typically introduces concepts in a traditional didactic approach and requires student memorization prior to application within practice settings. Additionally, many centers rely on best practices from abroad, due to lack of locally published laws and guidance documents. Objectives: The aim of this paper was to summarize and critically evaluate a professional skills laboratory designed to enhance learning through diversity in instructional methods relating to pharmacy law and best practices regarding narcotics, controlled medications, and benzodiazepines. Setting: This study took place within the Professional Skills Laboratory at the College of Pharmacy at Qatar University. Method: A total of 25 students participated in a redesigned laboratory session administered by a faculty member, clinical lecturer, teaching assistant, and a professional skills laboratory technician. The laboratory consisted of eight independent stations that students rotated during the 3-h session. Stations were highly interactive in nature and were designed using non-traditional approaches such as charades, role-plays, and reflective drawings. All stations attempted to have students relate learned concepts to practice within Qatar. Main outcome measures: Student perceptions of the laboratory were measured on a post-questionnaire and were summarized descriptively. Using reflection and consensus techniques, two faculty members completed a SWOC (Strengths, Weaknesses, Opportunities, and Challenges) analysis in preparation for future cycles. Results: 100% (25/25) of students somewhat or strongly agreed that their knowledge regarding laws and best practices increased and that their learning experience was enhanced by a mixed-methods approach. A total of 96% (24/25) of students stated that the mixed-methods instructional approach should be continued in the future. The SWOC analysis identified the mixed methods approach and student feedback as strengths and opportunities, while resource shortages and lack of impact assessment were identified as weaknesses and challenges. Conclusion: Creative redesign of instructional methods pertaining to law and best practices was effective to achieve positive student perceptions regarding instructional methods and learning. Future cycles should include rigorous assessment methods to evaluate impact on student learning and practice.